2008
DOI: 10.1128/jcm.02105-07
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Invasive and Colonizing Strains of Streptococcus agalactiae from Neonates of Six U.S. Academic Centers from 1995 to 1999

Abstract: The purpose of this study was to describe the population structure of group B streptococci (GBS) isolated from infected and colonized neonates during a prospective active-surveillance study of early-onset disease in six centers in the United States from July 1995 to June 1999 and to examine its relationship to bovine strains of GBS. The phylogenetic lineage of each GBS isolate was determined by multilocus sequence typing, and isolates were clustered into clonal complexes (CCs) using the eBURST software program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
85
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 36 publications
8
85
3
1
Order By: Relevance
“…A prevalence of 7 -25% GBS colonization in AV has been reported in women between 35 and 37 weeks of gestation 54 , with intrauterine infection associated with the ability of GBS to ascend from the lower genital tract and colonize the upper genital tract [54][55][56] . In the newborn, GBS infection may be congenital or acquired 22,57 and remains the foremost cause of neonatal mortality and morbidity in the world despite a recent decline in occurrence 48,52,58,59 . GBS early-onset disease (EOD) occurs at the age of 0-6 days and has been associated with the presence of GBS in the vagina of the mother with transmission thought to take place vertically through aspiration of infected amniotic fluid or passage through the birth canal [60][61][62] , while lateonset disease (LOD), occurs at age between 7 and 90 days 48,62,63 with the source of infection attributed to community or nosocomial acquisition 62 .…”
Section: Group B Streptococci (Gbs)mentioning
confidence: 99%
See 1 more Smart Citation
“…A prevalence of 7 -25% GBS colonization in AV has been reported in women between 35 and 37 weeks of gestation 54 , with intrauterine infection associated with the ability of GBS to ascend from the lower genital tract and colonize the upper genital tract [54][55][56] . In the newborn, GBS infection may be congenital or acquired 22,57 and remains the foremost cause of neonatal mortality and morbidity in the world despite a recent decline in occurrence 48,52,58,59 . GBS early-onset disease (EOD) occurs at the age of 0-6 days and has been associated with the presence of GBS in the vagina of the mother with transmission thought to take place vertically through aspiration of infected amniotic fluid or passage through the birth canal [60][61][62] , while lateonset disease (LOD), occurs at age between 7 and 90 days 48,62,63 with the source of infection attributed to community or nosocomial acquisition 62 .…”
Section: Group B Streptococci (Gbs)mentioning
confidence: 99%
“…The gastrointestinal tract serves as the natural reservoir for GBS and is expected to be the source of vaginal colonization 23,43 . Pregnant women who are colonized with GBS might develop infections of the urinary tract, bacteremia, chorioamnionitis, and postpartum endometritis 23,47,48 , thus increasing the risk of PTD, PPROM and perinatal transmission [49][50][51] , resulting in neonatal sepsis and meningitis 45,52,53 . A prevalence of 7 -25% GBS colonization in AV has been reported in women between 35 and 37 weeks of gestation 54 , with intrauterine infection associated with the ability of GBS to ascend from the lower genital tract and colonize the upper genital tract [54][55][56] .…”
Section: Group B Streptococci (Gbs)mentioning
confidence: 99%
“…Several studies have shown that serotype III strains belonging to ST-17 are more often associated with neonatal disease, indicating that ST-17 strains may be inherently more virulent than strains of other GBS lineages. [4][5][6][7][8] Additionally, a previous study that examined the GBS colonization status of pregnant women before and after delivery showed that serotype III ST-19 and ST-17 strains were more likely to persistently colonize women after receiving intrapartum antibiotic prophylaxis (IAP), whereas ST-12 strains were more frequently lost. 9 This ability of certain GBS STs to persist suggests an enhanced ability to evade the effect of antibiotics, either through enhanced antibiotic tolerance or protection via biofilm production or uptake into host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies of serotype V strains have investigated the noncapsular genetic makeup of the strains, and those that have done so have included colonizing and invasive GBS strains isolated from infants or have not described the clinical origin of the tested strains (18,19). Thus, we sought to analyze a large cohort of clinically well-defined, geographically distinct, and temporally disparate GBS isolates by using a whole-genome approach to elucidate the population structure of serotype V GBS causing invasive disease in nonpregnant adults.…”
mentioning
confidence: 99%